“CHOLG‘U IJROCHILIGI” VA “AN’ANAVIY XONANDALIK” TA’LIM YO‘NALISHLARIDA “SOLFEDJIO” FANINING O‘RNI (ART AND CULTURE BULLETIN, 2025)
This article discusses the role of solfeggio in the educational process of the higher education system today, its goals, objectives and practical significance. The article also reflects that the knowledge and skills gained in solfeggio classes are important for students in instrumental performance lessons and traditional singing, as well as in the study of other disciplines that complement their harmonious developing programs of musical art.
Keywords: mmusic and musical art; musical literacy; special subjects; musical taste; cal memory and thinking; musical and aesthetic education; synthesizer; microphone; stereo recordings; computer programs.